A Place-based response to Fikile Nxumalo - Motala, Siddique (Critical Studies in Teaching and Learning, 2023)
This paper is based on the response to Fikile Nxumalo’s keynote address at the 10th Annual New Materialism conference in Cape Town. It brings into conversation Nxumalo’s practice in early childhood education in North America, with my teaching practice situated in engineering education in Cape Town. Both practices are attuned to place and explore the generative potential of pedagogies that foreground coloniality and anti-black inheritances in context. Resonances between the practices are explored through feminist new materialisms, and I show how a combination of story and place may be utilised to resist dominant discourses from within engineering education.